Biocrystallization as a method for distinguishing between organically and conventionally produced milk - Anka Popović-Vranješ; Tijana Lopičić-Vasić; Goran Grubješić; Saša Krstović; Dragomir Lukač; Aleksandar Kralj; Uwe Geier (Mljekarstvo)
Holistic methods, such as biocrystallization and capillary dynamolysis, can be used to confirm differences in chemical composition between organic and conventionally produced milk. The utilization of such methods is complementary to other quality assurance methods and demonstrates a complex aspect of food quality. In this study, biocrystallization was used as a method for distinguishing between organic and conventionally produced pasteurized milk, demonstrating how the differences in the dairy cow feeding regime can affect milk properties. The biocrystallization was performed by means of copper (II) chloride dihydrate (CuCl2*2H2O). The biocrystallization patterns obtained from the conventional and organic milk samples were readily distinguished. A significant indication of differences was the emergence of degradation features in the biocrystallization patterns. While degradation features do not appear in organic milk, conventional milk showed clear indications of degradation, although the compound analysis of the two milks indicated no differences. From the morphological perspective, the biocrystallization patterns of organic milk have fared better according to all criteria. The results of the fatty acid analysis in milk from conventional and certified organic farms showed a greater content of beneficial fatty acids in organic milk: oleic (P<0.05), linoleic and linolenic (P<0.01). The analysis of animal feed indicated a higher content of cellulose, i.e. acid detergent fibers (ADF), and a lower content of neutral detergent fibers (NDF) in the organic animal feed. It was concluded that the method of copper chloride biocrystallization can determine the differences between pasteurized conventional and organic milk, which is greatly important in assuring the consumers of the milk origin, since the organic chain implies the increased quality control of soil, animal feed, animals and final dairy products with added value.